Pengembangan BUMG melalui Pelatihan Keuangan dan Peternakan di BUMG Gampong Siem Aceh Besar - Arfan, Rahmat; Puspita, Desy; Hasbi, Khairita; Aini, Zahriatul; Akbar, Indra; Ariansyah, Ricky; Endiyani, Endiyani; Irhami, Irhami (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2024)
This community service was conducted in international collaboration with the attendance of several polytechnics held in Gampong Siem Aceh Besar. This service is themed as BUMG and already exists in the village. From the observation results, it was found that currently, there are only two BUMGs that have existed in the fields of animal husbandry and savings and loans. Meanwhile, from the results of the analyses and discussions, it was found that the BUMG operations were not fully optimal, so some discussions inspired improvements to advance the BUMG. For example, in animal husbandry, a fermentation process can be used to handle feed problems and structured financial reports in the savings and loan business. In both business fields, human resource development is still needed so that the BUMG becomes a valuable institution in the community economy in accordance with the community's circumstances and culture.